2016
DOI: 10.1111/all.13000
|View full text |Cite
|
Sign up to set email alerts
|

Application of recombinant antigen 5 allergens from seven allergy-relevant Hymenoptera species in diagnostics

Abstract: Due to extensive cross-reactivity in various diagnostic settings, antigens 5 are inappropriate markers for differential sIgE diagnostics in vespid venom allergy. However, the newly available antigens 5 from further vespid species and the combination of recombinant allergen-based sIgE measurements with BAT represents a practicable way to diagnose clinically relevant sensitization in vespid venom allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 42 publications
3
66
0
3
Order By: Relevance
“…One interesting candidate, Pol d 4, which was identified in P. dominula venom but not in Vespula venom, failed as marker allergen due to low sensitization prevalence in Polistes sensitized individuals (unpublished data). All other Polistes allergens that have been described so far, have a homologous counterpart in Vespinae venom and display a high degree of peptide-based cross-reactivities [27], making them unsuitable for precise discrimination of YJV or Polistes sensitizations.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…One interesting candidate, Pol d 4, which was identified in P. dominula venom but not in Vespula venom, failed as marker allergen due to low sensitization prevalence in Polistes sensitized individuals (unpublished data). All other Polistes allergens that have been described so far, have a homologous counterpart in Vespinae venom and display a high degree of peptide-based cross-reactivities [27], making them unsuitable for precise discrimination of YJV or Polistes sensitizations.…”
Section: Figmentioning
confidence: 99%
“…Due to these structural similarities, venom PLA1 and antigen 5 have limited diagnostic value for discrimination of Vespula and Polistes sensitizations [13,17]. A recent study showed significant levels of peptide-based cross-reactivity between antigen 5 from several members of Vespinae and Polistinae [27]. Venom PLA1 were shown to cross-react to a lesser extent [10,36].…”
Section: Component-resolved Diagnostics and Peptide Based Cross-reactmentioning
confidence: 99%
See 1 more Smart Citation
“…stings of the different vespid species is still challenging [37,64,65]. Unique marker allergens that would allow reliable discrimination are not available and, to our opinion, will be hard to find due to the close phylogenetic distance of the species.…”
Section: Accepted Articlementioning
confidence: 99%
“…Estima-se que cerca de 50% dos doentes com alergia ao veneno destes insetos apresentem resultados positivos, TC e/ou IgE esp, tanto para veneno de abelha (Apis mellifera) como para veneno de vespa (Vespula germanica e Polistes dominula, as duas principais espécies no nosso país) 1,2 . Por outro lado, alguns autores descrevem que mais de 30% dos doentes com RS à picada de insetos apresentam TC e IgE esp negativos, provavelmente devido à sensibilidade limitada destes métodos 3 . A dupla positividade para veneno de abelha e veneno de vespa pode representar uma verdadeira dupla sensibilização ou reatividade cruzada a ambos os venenos devido à homologia de sequência entre proteínas destes venenos, tais como hialuronidases ou mesmo determinantes dos carboidratos (CCD).…”
unclassified